Small differences in turn cycle structure assessed through an IMU could be decisive to enhance descent performance of elite alpine skiers in different slalom course settings - Pérez-Chirinos Buxadé, C.; Padullés Riu, J. M.; Gavaldà Castet, D.; Trabucchi, M.; Fernández-Valdés, B.; Tuyà Viñas, S.; Moras Feliu, G. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: Competitive alpine skiing is a sport that occurs between 40 and 150 km/h. At that speed, there are many details that could go unnoticed by coaches, especially when the differences between skiers are fractions of a second. Small differences in turn cycle structure translates into better performance on the turn. However, the influence on performance along a ski run (linked curves) has not been investigated yet. The aim of this study was to assess the influence of turn cycle structure on the performance of elite alpine skiers using an inertial measurement unit (IMU) in different slalom (SL) course settings.